Structural Priming and Inverse Preference Effects in L2 Grammaticality Judgment and Production of English Relative Clauses - Wei, Ran; Kim, Sun-A; Shin, Jeong-Ah (Frontiers in Psychology, 2022)
This study investigated inverse preference effects in L2 structural priming of English relative clauses and their potential influences on subsequent learning of target structures. One hundred fourteen Chinese learners of English at a low-to-intermediate proficiency level participated in a structural priming experiment with a pretest-posttest design. The experimental group underwent a priming task in which they orally produced syntactic structures immediately after viewing English object or passive relative clauses as primes, whereas the control group only read sentences unrelated to English relative clauses. A grammaticality judgment test and a sentence completion test were used to measure the inverse preference effect and its subsequent effects on L2 learning. The results showed the presence of structural priming and inverse preference effects in immediate production, which extended to subsequent L2 learning. In subsequent grammaticality judgments and production, L2 learners performed well with a greater degree with English object relative clauses than for English passive relative clauses in comparison to the pretest. The results are discussed in terms of the structural frequency in both L1 and L2 as well as the implicit learning mechanisms of structural priming.